2022
DOI: 10.3389/fchem.2022.1076383
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of new thiazolidinone/uracil derivatives as antiproliferative agents targeting EGFR and/or BRAFV600E

Abstract: Thiourea derivatives of uracil were efficiently synthesized via the reaction of 5-aminouracil with isothiocyanates. Then, we prepared uracil-containing thiazoles via condensation of thioureas with diethyl/dimethyl acetylenedicarboxylates. The structures of the products were confirmed by a combination of spectral techniques including infra-red (IR), nuclear magnetic resonance (NMR), mass spectrometry (MS) and elemental analyses. A rationale for the formation of the products is presented. The newly synthesized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The in vitro anti-BRAF V600E activity of compounds 3a–e was further investigated [ 38 ] using erlotinib and vemurafenib as reference compounds and results are shown in Table 2 . The enzyme assay revealed that the five compounds tested significantly inhibited BRAF V600E , with IC 50 ranges from 35 to 67 nM, Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro anti-BRAF V600E activity of compounds 3a–e was further investigated [ 38 ] using erlotinib and vemurafenib as reference compounds and results are shown in Table 2 . The enzyme assay revealed that the five compounds tested significantly inhibited BRAF V600E , with IC 50 ranges from 35 to 67 nM, Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The activity of 3a–e against BRAF was investigated using a V 600E mutant BRAF kinase assay [ 38 ]. See Appendix SA (Supplementary Materials) .…”
Section: Methodsmentioning
confidence: 99%
“…The synthesised derivatives were evaluated for its in vitro anti-proliferative activity against eight cancer cell lines cervical (Hela), colon (Colo-205), lung (A-549), leukaemia (HL-60), ovarian (SKOV-3) and breast (MDA-MB-231, MCF-7 and T47D) cancer cell lines. [55] It was observed that compound 71 c exhibited potent anti proliferative activity against T47D cells with IC 50 value 7.56 � 0.29 μM as compared to the control staurosporine with IC 50 value 4.52 � 0.9 μM.…”
Section: Introductionmentioning
confidence: 97%
“…Following our previous study on dual targeting strategies and motivated by the findings above [ 40 , 41 , 42 ], we synthesized new spiro-compounds that combine quinolinone, thiazolidinone, and spiro-cyclic in a single molecule via the reaction of thioglycolic acid and 4-(2-cyclodenehydrazinyl)4uinoline-2(1 H )-one. As a result, two new compounds, 6a – e (Scaffold A) and 7a and 7b (Scaffold B), were developed to generate new potent antiproliferative agents targeting EGFR and/or BRAF V600E , as shown in Figure 3 .…”
Section: Introductionmentioning
confidence: 99%